ANALISIS MENGENAI PENGARUH POLITIK TERHADAP KEHIDUPAN DI KAMPUNG YEFLIO DISTRIK MAYAMUK KABUPATEN SORONG - Aswad Muhdar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
Freedom of autonomy in the village there is political space provided by the government through political institutions, political institutions become a channel of communication, in conveying the will and aspirations of the village community in political life. However, political institutions are also limited to those who are considered to have an interest, while in reality political participation is that a large part of the community must take part in the process of political maturation. So the only way to provide understanding and insight for the community in the village is through an understanding of the influence of politics in people's lives. This type of research uses descriptive qualitative methods using data collection techniques through observation, interviews, and documentation. Based on the results of the study, it can be concluded: That the analysis of political influence on people's lives in Yeflio village, Mayamuk District, Sorong Regency still needs to increase political influence and socialization of the community about the purpose of holding politics so that the Yeflio village community, Mayamuk District, Sorong Regency can accept their candidates without anarchy. because the other candidates failed in the competition, the need to increase human resources by providing delivery of learning assignments, training and courses. In accordance with what is expected by the community, which has not achieved optimal results because the political influence of human resources is still lacking and needs to be improved again.